Servol pre-school and adolescent training programmes in Trinidad and Tobago - Mahabir, Diana (International Institute for Educational Planning ParisFR, 1993)
Servol, a non-governmental community-development organization provides an effective system of pre-school education and programmes to assist adolescent drop-outs in attitudinal development and parenting skills. This publication looks at the basic education system; development of the innovation; development and implementation of collaboration; and achievements of Servol. Makes conclusions and recommendations.